2017
DOI: 10.1075/is.18.1.04kis
|View full text |Cite
|
Sign up to set email alerts
|

Prelinguistic gesture use in mother-infant and mother-infant-sibling interactions

Abstract: I tested the hypothesis that, in infant-mother-sibling interactions, infants with older siblings aged 11 to 24 months produce deictic gestures when they are proximal to, or engaging in joint attention with, their mothers more frequently than same-aged infants without siblings. Fifteen infant-mother dyads and 10 infant-mother-sibling triads were individually observed for 15 minutes in a playroom full of toys. Infants involved in infant-mother-sibling interactions produced more deictic gestures when they were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…En esta misma línea otros trabajos compararon las interacciones diádicas entre la madre y el niño con interacciones triádicas entre la madre, el niño y un hermano y encontraron que cada contexto de interacción puede impactar de forma distinta en el desarrollo lingüístico de los niños pequeños (Kishimoto, 2017;Malmeer & Assadi, 2013). Por ejemplo, Benigno et al (2007) encontraron que en los contextos triádicos niños de 20 meses buscaban ellos mismos generar los episodios de atención conjunta con sus madres, probablemente porque debían compartir la atención materna con su hermano.…”
Section: Las Palabras De Otros Niños En El Entorno Lingüístico De Beb...unclassified
See 1 more Smart Citation
“…En esta misma línea otros trabajos compararon las interacciones diádicas entre la madre y el niño con interacciones triádicas entre la madre, el niño y un hermano y encontraron que cada contexto de interacción puede impactar de forma distinta en el desarrollo lingüístico de los niños pequeños (Kishimoto, 2017;Malmeer & Assadi, 2013). Por ejemplo, Benigno et al (2007) encontraron que en los contextos triádicos niños de 20 meses buscaban ellos mismos generar los episodios de atención conjunta con sus madres, probablemente porque debían compartir la atención materna con su hermano.…”
Section: Las Palabras De Otros Niños En El Entorno Lingüístico De Beb...unclassified
“…Other research along the same lines compared the dyadic interactions between mother and child with triadic interactions between mother, young child and sibling, and found that each context can have a different impact on the linguistic development of young children (Kishimoto, 2017; Malmeer & Assadi, 2013). For example, Benigno et al (2007) found that in triadic contexts 20-month-olds themselves actively sought joint attention with their mothers, most likely due to having to share maternal attention with their sibling.…”
mentioning
confidence: 99%
“…1.2 | Gesture use and language development outside the Western context Although research on caregivers and children's use of gesture has been done mostly with families from Western countries, there is an emerging line of international and cross-cultural research observing early gesture use in different cultural settings (e.g., Callaghan et al, 2011;Cameron-Faulkner et al, 2021;Goldin-Meadow & Saltzman, 2000;Haviland, 1998;Kishimoto, 2017;Kita, 2009;Kwon et al, 2018). Such studies have started to provide evidence of both similarities and variations across different cultural contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing efforts to examine parents’ and children’s use of gesture in different cultural contexts (e.g., Kishimoto, 2017; Liszkowski et al., 2012; Salomo & Liszkowski, 2013), most of what we know about this mode of communication is still largely based on a small subset of the population of Western countries. Such an approach limits our understanding of the role that culture plays in children’s early experiences and development (Henrich et al., 2010; LeVine, 2004; Schieffelin & Ochs, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation